Wind tunnel data for knitted windbreak prototypes - Hörteborn, Erica (Chalmers University of Technology, 2022)
This data was gathered for a study that focused on knitted textiles since they have several properties that offer potentials for wider applications within the built environment. Particularly, two features of the knitted structure are key in this study. Firstly, the loop-structure of the knit that enables the creation of three-dimensionality both on a surface level as well as on an architectural scale without cutting and sewing. Secondly, the ability to easily incorporate a varying porosity in the design of the knitted textile.
Knitted textiles, employed as windbreaks in the urban space could contribute to the creation of high-quality outdoor environments, where design informed by the local wind conditions can add both character and satisfactory wind comfort to a space. In this study, results from wind tunnel tests at an early design stage are presented, with the focus on determining the effectiveness of drop-stitch knits with diverse porosities in terms of reducing wind speed. The overarching purpose is to show the potential of this type of structure and indicate, through a comparative study of knitted prototypes, important design aspects and knit patterns best suited for improving wind comfort.

The measurements were performed in a wind tunnel at Chalmers University of Technology. It is a closed-loop low-turbulence wind tunnel with a cross-sectional dimension of the test section of 1.8 m x 1.25 m. The wind tunnel has good flow uniformity (better than 1 %) and high flow stability. The incoming flow velocity was measured by a high-accuracy digital micromanometer with 0.5% accuracy. The micromanometer was connected to a Prandtl tube located in the wind tunnel inlet, approximately at a two-meter distance from the model. The air density was evaluated from the flow temperature and absolute pressure with 0.5% accuracy. The aerodynamic forces acting on the models were measured by a six-component balance with 1% accuracy. Only the drag force component was analysed in this study. The flow velocity behind the model was measured by a hot film anemometer from Dantec Dynamics with an accuracy of over 2 %. The anemometer was measuring the streamwise wind velocity without distinguishing the direction.
All the models were mounted on a steel frame, with all members having a circular cross-section of 10 mm. The frame was mounted on a six-component balance located under the floor outside of the wind tunnel test section. The top and bottom of the textiles were held in place by a smaller steel rod (diameter: 3 mm and 2 mm). The total weight of the frame was 966 g.
The upstream velocities were approximately 3.5, 6, 8, 12.5 and 15 m/s (the slight variation between the test, was due to the blockage). These velocities correlate to the Beaufort scales of 3, 4, 5, 6 and 7, corresponding to a range from a gentle breeze to near gale. These values were measured for each test, resulting in minor differences each time. The models were tested at 4 different angles relative to the wind direction: 90°, 70°, 45°, and 20°.
The wind speed downstream was measured with a hot-film anemometer at a position that would correlate to 5/8 H, where H is the screen's height.

The porosity for the knitted models was calculated through analysing digital photographs of the knits, mounted on the frames to get the initial stretch, and then using a script to analyse the images in a Java-based programming environment Processing. The porosity is calculated as the number of sufficiently light pixels divided by the number of all pixels in the photograph.

Data are provided in an excel-file SharedDataWindtunnelTestsKnittedStructures_2022-11-07.xlsx, with the variables explained in the documentation file ReadMeWindTunnelTestsKnittedStructures.txt

The measurements were performed in a wind tunnel at Chalmers University of Technology. It is a closed-loop low-turbulence wind tunnel with a cross-sectional dimension of the test section of 1.8 m x 1.25 m. The wind tunnel has good flow uniformity (better than 1 %) and high flow stability. The incoming flow velocity was measured by a high-accuracy digital micromanometer with 0.5% accuracy. The micromanometer was connected to a Prandtl tube located in the wind tunnel inlet, approximately at a two-meter distance from the model. The air density was evaluated from the flow temperature and absolute pressure with 0.5% accuracy. The aerodynamic forces acting on the models were measured by a six-component balance with 1% accuracy. Only the drag force component was analysed in this study. The flow velocity behind the model was measured by a hot film anemometer from Dantec Dynamics with an accuracy of over 2 %. The anemometer was measuring the streamwise wind velocity without distinguishing the direction.
All the models were mounted on a steel frame, with all members having a circular cross-section of 10 mm. The frame was mounted on a six-component balance located under the floor outside the wind tunnel test section. The top and bottom of the textiles were held in place by a smaller steel rod (diameter: 3 mm and 2 mm). The total weight of the frame was 966 g.
The upstream velocities were approximately 3.5, 6, 8, 12.5 and 15 m/s (the slight variation between the test, was due to the blockage). These velocities correlate to the Beaufort scales of 3, 4, 5, 6 and 7, ranging from a gentle breeze to near gale. These values were measured for each test, resulting in minor differences each time, as can be seen in the graphs in the result section. The models were tested at 4 different angles relative to the wind direction: 90°, 70°, 45°, and 20°. The wind speed downstream was measured with a hot-film anemometer at a position that would correlate to 5/8 H, where H is the height of the screen.
All tests were filmed to catch the movement of the prototypes and the wind. Video files are available upon request.

Denna data är från mätningar i vindtunnel för stickade textila vindbarriärprototyper. Även beräknad optisk porositet för protyperna presenteras.
Syftet med studien är att utvärdera stickade textiliers användbarhet i avseende att förbättra vindkomfort i urbana miljöer. Det är främst två saker som gör stickade textilier intressanta i detta avseende. För det första så kan man genom uppbyggnaden av stickningen skapa en tredimensionalitet både på micro-nivå och macro-nivå. För det andra så kan en variation i densitet enkelt kombineras i en stickad textil, utan att behöva sy och klippa tyget. Studien och resultaten är från ett tidigt studie och ska ses som en grund för vidare forskning inom området.
Mätningarna gjordes i en fysisk vindtunnel på Chalmers.
(mer detaljerad beskrivning finns i katalogen på engelska)
Vindtunnelmätningar för stickade vindbarriärprototyper
Keywords: textiles; wind tunnel tests; Architectural Engineering; Arkitekturteknik; Fluid Mechanics; Strömningsmekanik